Chemical composition and antioxidant, antimicrobial and haemolytic activities of crambe cordifolia roots - Rashid, Muhammad Abid; Akhtar, Muhammad Nadeem; Ashraf, Aisha; Nazir, Sadia; Ijaz, Anum; Noradila, Abdullah Omar; Noor, Sadia; Basit, Abdul; Tareen, Rasool Bakhsh (Romanian Society for Pharmaceutical Sciences, 2018)
In the current study, we investigated the chemical composition, in vitro antioxidant, antimicrobial and haemolytic activities of the crude (methanolic) and n-hexane, chloroform, and ethyl acetate extracts of roots of Crambe cordifolia Steven. The GC-MS analysis led to identification of erucic acid (20.8%), p-cymene (20.9%), palmitic acid (19.2%) and vitamin E (13.8%) as major components of methanol, n-hexane, chloroform and ethyl acetate extracts respectively. The results of spectrophotometric assays showed that the methanol extract had the highest total phenolic contents (210.3 ± 0.74 μg GAE/mg of dry plant material), total flavonoid contents (75.5 ± 0.32 μg QE/mg of dry plant material) and antioxidant potential. It was established by disc diffusion and minimum inhibitory concentration methods that, overall, the methanol extract exhibited the highest antimicrobial activity against most of the tested microbial strains (Escherichia coli, Bacillus subtilis, Pasteurella multocida, Staphylococcus aureus, Aspergillus niger and Fusarium solani) as compared with the nhexane, chloroform, and ethyl acetate extracts. The outcome of the haemolytic assay showed that the tested extract and different solvent fractions were safe to human erythrocyte membrane